Innovation in hydrogen production - Dincer, Ibrahim; Acar, Canan (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, the critical perspectives of innovation are introduced for specifically for hydrogen production under a new concept (so-called: 18S concept), covering source, system, service, scope, staff, scale-up, safety, scheme, sector, solution, stakeholder, standardization, subsidy, stimulation, structure, strategy, support and sustainability. The roles of these specific conceptual items are discussed, and their importance is highlighted. Furthermore, the innovative methods in hydrogen production are assessed by using a ranking method for comparison and evaluation purposes. The results show that renewable sources, particularly hydro, geothermal and solar show a unique potential to support these innovative H-2 production systems. When the H-2 production systems are compared, the ones supporting heat recovery (thermal) and the photonic based options show better performance in terms of emissions, cost and efficiency. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Innovation; Hydrogen production; Energy; Environment; Sustainability; Renewables; PHOTOCATALYTIC ACTIVITY; SYNGAS PRODUCTION; SOLAR; WATER; BIOMASS; GASIFICATION; CYCLE; LIGHT; FUEL; Chemistry; Electrochemistry; Energy & Fuels